Communal kitchen: food as a catalyst for improved community development and interaction - Themistocleous, Harry Mark (My University, 2012)
Food does many things: it nourishes the body and feeds the soul; it brings people together; it builds on tradition and enhances culture. But food can do so much more. In conjunction with architecture, food can create place, it can uplift communities, improve economies and enhance life. The amalgamation of food and architecture creates a wealth of opportunities for both the exploration of space creation and opportunities for improved community development. It is with the understanding of this intersection that one is able to reassess the process and production of architecture and transform its often disconnected nature into something which can act as a catalyst for change within a community; a solution which enables the built form to become accessible, desirable and most importantly, functional. Through the study of food and architecture and their inextricable link, this thesis aims at creating a new typology for communal interaction in the heart of Kliptown. A facility will be created with the intention of enabling the cultural and economic upliftment of the area by providing key facilities based on the interaction between food and architecture in the form of communal cooking facilities, fresh produce markets as well as a dining component. In doing so, one is able to create new, practical, architectural solutions to assist this struggling community by creating opportunities for financial independence, improved nutrition, desirable interactive public space as well as addressing the growing need for sustainability.